The Effect of Medical Marijuana Laws on the Labor Supply of Older Adults: Evidence from the Health and Retirement Study - Lauren Hersch Nicholas; J. Catherine Maclean (Institute of Labor Economics (IZA), 2017)
We study the effect of state medical marijuana laws on labor supply among older adults; the demographic group with the highest rates of many health conditions for which marijuana may be an effective treatment. We use the Health and Retirement Study to study this question and estimate differences-in-differences regression models. We find that passage of a state medical marijuana law leads to increases in labor supply among older adults. These effects should be considered as policymakers determine how best to regulate access to medical marijuana.
Keywords: I10; I18; J20; 330; older adults; labor supply; medical marijuana; regulation; medication